Agarose-paraffin double embedding assisted with 3D printing for high throughput rice root sectioning - Van Anh, Le Thi; Dinh Phuc, Hoang; Huong Giang, Nguyen; Quynh Trang, Pham; Ho Nguyen, Le; Mai Quynh, Nguyen; Mai Huong, To Thi (Vietnam Journal of Biotechnology, 2022)
Anatomical analysis of the plant tissues is an important technique used in plant research for studying the process of plant growth, development, adaptation to environmental stress as well as for characterizing gene localization. In Vietnam, most anatomical analysis for plant material was manually conducted which is time-consuming and labor-intensive. In this report, we present an innovative method that can deliver high-quality rice root sectioning. To optimize the efficiency of the conventional paraffin sectioning technique, the agarose-paraffin double embedding was assisted with 3D-printing technique for designing the specific mold which allow to fix from 3 to 12 rice roots in agarose. Molds consist of a lower section with grooves for firmly holding the rice roots in the right place, the additional middle sections allowing up to 3 layers of root samples to be inserted and an upper section to hold the samples before pouring the embedding. The agarose blocks obtained from the molds were then fixed in the formalin solution, then dehydrated through a gradient concentration of ethanol before being impregnated through a series of mixtures of paraffin/xylene and finally embedded in the paraffin. Anatomical sections of 10 μm of thickness were cut with a microtome, spread on glass slides, and then used for staining and collecting the images. As a result, the agarose-paraffin double embedded tissue blocks were more easily orientated and better solidified for rapid and high-quality sectioning. The sections also showed no interference of agarose with staining, as result, the tissues were much clear. In conclusion, this method represents an innovative technique for high throughput plant sectioning which could be applied to different types of plant tissues.